Efficiency and Safety of Aftercare With Intrathecal Baclofen on Location. Issue 7 (18th August 2019) - Goslinga‐van der Gaag, Simone M.E.; Delhaas, Elmar M.; Frankema, Sander P.G.; Huygen, Frank J.P.M.
Abstract : Objectives: Patients with intractable spasticity treated with intrathecal baclofen (ITB) need regular evaluation and aftercare in an outpatient clinic or pain clinic setting. Logistically, this can be challenging. A solution could be to perform treatment at the patient's home setting. In the Netherlands, a project of the Dutch Healthcare Authority was initiated to deliver ambulatory ITB‐related services via a home‐based Ambulant Care Clinic. This aftercare is performed by nurse practitioners (NP) with support from a medical specialist. The scope of the study was to investigate the efficiency and safety of ITB‐care for patients with severe disabling spasticity in their home setting. Materials and Methods: A retrospective analysis of prospectively collected data. Patients with congenital or acquired spasticity were treated with ITB (1st April 2011 to January 1st 2016) using an implanted programmable pump system were referred to the home‐based Ambulant Care Clinic by various neuromodulation centers in the Netherlands. All study parameters were a part of the standard intake and follow‐up documentation. Results: Of the 900 patients treated with ITB in the Netherlands, 239 were referred to the home‐based Ambulant Care Clinic and included in this study. Mean age was 45.5 (range 7–82) years; 52% lived at home; the average satisfaction score was 9 (scale 0–10); and 0.29% had (serious) adverse events (60% of clinical manifestations were prevented by remote double‐check control). Certifications for patient safety and quality standards were obtained. Conclusions: The concept of ITB aftercare on location demonstrated efficacy and safety in the described setting. For troubleshooting, close collaboration with a neuromodulation center is necessary and can be arranged in chain‐based care.